India : Promoting Agricultural Growth in Maharashtra, Volume 2. Annexes and Statistical Tables - World Bank (Washington, DC, 2013)
Fostering more rapid rural development, particularly raising the productivity and competitiveness, and accelerating the growth of the agricultural and rural non-farm sectors, and critical elements to achieving faster overall economic growth, and hence, poverty reduction in Maharashtra. This policy note focuses on examining the constraints to promoting more rapid agricultural growth in Maharashtra. It aims to: 1) review the recent status and performance of the agricultural sector in the State, focusing on selected key areas such as cotton, sugar, water, and the rural non-farm sector; 2) examine the major policy and regulatory impediments in these sub-sectors that hinder their contribution to more rapid and sustained agricultural growth and rural poverty alleviation; and 3) propose options for improvement in these areas as well as identify areas requiring further study. A second volume provides more detailed discussion on the Government of India Sugar Policy (Annex A), development schemes of the National Horticulture Board (Annex B), and basic principles for supply chain development and additional statistical tables.